Walk the talk: ESG mutual fund voting on shareholder proposals - Dikolli, Shane S.; Frank, Mary Margaret; Guo, Zhe Michael; Lynch, Luann J. (Review of Accounting Studies, 2022)
Abstract We document that U.S. mutual funds with investment objectives designated as “Sustainable Investment Overall” by Morningstar (ESG funds) are more likely than other mutual funds to vote in support of environmental and social (ES) shareholder proposals and governance (G) shareholder proposals. We also find that the higher support for ES proposals by ESG funds relative to other funds is more pronounced in index funds than in active funds, consistent with trading constraints influencing voting behavior. While these results provide evidence that ESG funds “walk the talk” with their voting behavior on average, we find that fund families play a significant role in that walk. Additionally, in an analysis of fund families that are signatories of the United Nations Principles for Responsible Investment (PRI), we find that ESG funds of PRI families are significantly more likely to support ES proposals and G proposals than non-ESG funds of PRI families. We determine that this significant difference stems from non-ESG funds of PRI families providing less support than non-ESG funds from non-PRI families. Taken together, these results provide evidence that ESG funds available to U.S. investors provide more support for shareholder proposals aligned with their designated investment objective, but the type and family of the fund influence that support.